Hypercalcaemia: An Extremely Rare Presentation of Hepatosplenic T-Cell Lymphoma - Ramalho, Sara Almeida (Eur J Case Rep Intern Med, 2021)
Hypercalcaemia is a frequent finding in malignancies including lymphomas. However, there are no reports of hypercalcaemia in hepatosplenic T-cell lymphoma (HSTCL). HSTCL is a rare and aggressive neoplasm which is usually difficult to diagnose. We present a case of HSTCL in which hypercalcaemia was the initial presentation. LEARNING POINTS: Hepatosplenic T-cell lymphoma (HSTCL) is difficult to diagnose, has a poor prognosis and usually presents with hepatosplenomegaly, B symptoms and cytopenias. Hypercalcaemia is an extremely rare clinical presentation of HSTCL. Severe hypercalcaemia is a life-threatening condition and should always be corrected and investigated.